The Europen Economic and Monetary Union, the Czech republic and the Theory of Optimum Currency Areas - Jurák, Jan; Brůžek, Antonín, 1929-2008; Amort, Jiří; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2006)
The paper explores the theory of optimum currency areas, outlines its implications for current international monetary order, and applies its conclusions to the European Economic and Monetary Union
Vedoucí práce: Antonín Brůžek
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2007
Rok obhajoby 2007
Keywords: mezinárodní a evropská studia - diplomacie [obor dipl. práce]; diplomové práce; master's theses